Strategi Pengembangan Pariwisata Berkelanjutan Oleh Dinas Pariwisata dan Kebudayaan Kabupaten Pangandaran - Ita Sri Wahyuni; Sirodjul Munir (Jurnal Hukum dan Sosial Politik, 2025)
This research is motivated by the suboptimal strategy of the Pangandaran Regency Tourism and Culture Office in supporting sustainable tourism development. Several problems identified include the lack of optimal management of facilities and infrastructure, such as waste management, and inadequate transportation facilities. Furthermore, tourism promotion has not been carried out in a sustainable and measurable manner, compounded by the absence of a Regional Promotion Agency. Human resources (HR) in the tourism sector also still lack a comprehensive understanding of the concept of sustainable tourism, which is a major challenge in implementing this policy effectively. The purpose of this study was to determine the strategies implemented by the Pangandaran Regency Tourism and Culture Office in developing sustainable tourism. The method used was descriptive qualitative with data collection techniques through observation, interviews, and documentation. Informants in this study consisted of government elements, communities, and tourism business actors. The results showed that the strategies implemented by the Pangandaran Regency Tourism and Culture Office encompass four dimensions of strategic management: environmental monitoring, strategy formulation, strategy implementation, and evaluation and control. However, the strategies that have been implemented have not been optimal. Several efforts have been made, including increased training based on local potential, technology education, the formation of promotional groups, and regular activity evaluations. However, major challenges remain: strengthening coordination between various stakeholders and improving natural resource management and more environmentally friendly supporting facilities. This study illustrates the need for strategic and policy adjustments to optimize sustainable tourism development in Pangandaran Regency, with a focus on increasing understanding and involvement of the community and businesses, as well as optimizing infrastructure and promoting more planned and measurable initiatives.